The Role of Instagram Usage Intensity on Body Dissatisfaction in Adolescent Girls in Denpasar with Self-Esteem as a Moderating Variable - Widiastuti, Ni Nyoman Eri; Wulanyani, Ni Made Swasti; Shaheen, Shabeena (Yayasan Sinergi Kawula Muda, 2023)
Social media significantly influences the formation of the ideal body image. The discrepancy between the ideal body image and the current body reality causes adolescents to experience body dissatisfaction. However, the extent to which the impact of the pressure of the sociocultural model will depend on the individual's self-esteem. The study aims to determine the role of the intensity of Instagram use on body dissatisfaction in female adolescents in Denpasar, which is moderated by self-esteem. Sampling was carried out using a two-stage cluster sampling technique. The subjects in this study were 110 young women aged 10-22 years in Denpasar. The measurement tools used are Instagram Usage Intensity Scale, Self-Esteem Scale, and Body Dissatisfaction Scale. The results of the Moderated Regression Analysis (MRA) test show a parameter coefficient value of 1,791 with a significance of 0.004 (p <0.05), meaning that the intensity of Instagram use plays a significant role in body dissatisfaction. The coefficient value of the self-esteem moderation parameter is -0.012 with a significance of 0.039 ( p <0.05), meaning that self-esteem weakens the relationship between the intensity of Instagram use and body dissatisfaction. The coefficient of determination (R2) in this study was 0.392, meaning that the intensity of using Instagram and self-esteem played a role of 39.2% in body dissatisfaction. The results of this study can provide a general description of the role of the intensity of Instagram use on body dissatisfaction which can be moderated by self-esteem.